Optical Properties of 1D ZnO/MoS\(_2\) Heterostructures Synthesized by Thermal Evaporation Method - Luu, Thi Ha Thu; Do, Quang Trung; Tran, Manh Trung; Nguyen, Tu; Nguyen, Duy Hung; Pham, Thanh Huy (Communications in Physics, 2022)
MoS2 material attracts a great attention from researchers due to its graphene-like structure and the bandgap difference between its hexagonal monolayer and bulks. Recently, ZnO/MoS2 heterostructures have been received significant interest due to their distinguished properties. In this study, one-dimensional ZnO and ZnO/MoS2 heterostructures were successfully synthesized by a thermal co-evaporation method. Compare with ZnO, the band-to-band emission of ZnO/MoS2 heterostructures establishes a “blueshift” towards a shorter wavelength. It could be explained by the lattice strain in ZnO/MoS2 heterostructures due to the difference of primitive cell of ZnO and MoS2. Additionally, the quench in the visible region of the PL spectrum of ZnO/MoS2 heterostructures also explains the reduction of the defect in ZnO due to the presence of MoS2.